Pneumatosis cystoides intestinalis linked to sunitinib treatment for renal cell carcinoma. Issue 6 (17th September 2019) - Shikuma, Hiroyuki; Inoue, Shogo; Hatayama, Tomoya; Mukai, Sakurako; Muto, Masayuki; Miyamoto, Shunsuke; Sadahide, Kosuke; Fujii, Shinsuke; Sekino, Yohei; Goto, Keisuke; Shinmei, Shunsuke; Hieda, Keisuke; et al.
Abstract : Introduction: Pneumatosis cystoides intestinalis is a rare condition characterized by air‐filled cysts within intestinal walls. It can be caused by various factors. We report a case of pneumatosis cystoides intestinalis linked to sunitinib treatment for renal cell carcinoma. Case presentation: A 67‐year‐old female with advanced renal cell carcinoma who had been treated with sunitinib visited our hospital complaining of abdominal pain. Computed tomography scans showed diffuse air‐filled cystic formation of intestine. We treated with conservative therapy, and she recovered. However, although air‐filled cysts disappeared in the images, intraoperative findings in the resection of a recurrent paracaval lymph node showed a thinning of the intestine. Conclusion: It is necessary to consider pneumatosis cystoides intestinalis when a patient using a tyrosine kinase inhibitor complains of abdominal symptoms. It should also be noted that the effect of pneumatosis cystoides intestinalis may remain even if pneumatosis disappears from the image on tomography scans.